(untitled) (CIPEEX, 2022)
&NBSP; THE FOLLOWING TEXT REFERS TO AN EXPERIENCE REPORT ABOUT THE PERFORMANCE OF A GROUP OF ACADEMICS OF THE DENTISTRY COURSE IN THE UNIVERSITY EXTENSION PROJECT - UNIEVANGLICA ITINERANT CITIZEN. UNIEVANGELICA PARTICIPATED IN THE CELEBRATIONS OF THE 15 YEARS OF THE INSTITUTE OF SOCIAL SECURITY OF ANAPOLIS - ISSA, LINKED TO THE LOCAL CITY HALL. THIS PROJECT INVOLVES FIVE COURSES OF THIS INSTITUTION, AMONG THEM, DENTISTRY. THE ITINERANT CITIZEN EXTENSION PROJECT CONSOLIDATES THE SERVICE TO THE BROADER DEMANDS OF THE COMMUNITY AND CONTRIBUTES TO LOCAL AND REGIONAL SOCIAL DEVELOPMENT. SOME STUDENTS AND PROFESSORS PROVIDED CARE TO THE RETIREES, PENSIONERS AND SERVERS OF THE MUNICIPALITY. A LECTURE WAS GIVEN ON ORAL CANCER PREVENTION AND EXAMINATIONS FOR THE DIAGNOSIS OF ORAL CAVITY DISORDERS. THE WORK CARRIED OUT HAS UNDERGONE AN EXCHANGE OF VALUES €‹€‹BETWEEN THE UNIVERSITY AND THE COMMUNITY, WHICH CONTRIBUTES TO THE COMPLETE FORMATION OF THE DENTIST-SURGEON, CRUCIAL TO PUT INTO PRACTICE THE ACQUIRED SCIENTIFIC KNOWLEDGE, IN NON-FORMAL PLACES. &NBSP; PALAVRAS-CHAVE (OU KEYWORDS, OU PALABRAS CLAVE): DENTISTRY, OLD AGE ASSISTANCE, HEALTH PROMOTION